Impact of COVID‐19 pandemic on surveillance of hepatocellular carcinoma: A study in patients with chronic hepatitis C after sustained virologic response - Toyoda, Hidenori (GastroHep, 2020)
BACKGROUND: The current coronavirus disease 2019 (COVID‐19) pandemic has strongly influenced many aspects of the medical care, including cancer surveillance. AIMS: We investigated how the COVID‐19 pandemic influenced surveillance for hepatocellular carcinoma (HCC), focusing on patients with hepatitis C virus infection who were receiving surveillance for HCC after sustained virologic response (SVR) in Japan. METHODS: Patients who achieved SVR between 1995 and 2017 and continued receiving surveillance were compared by month in terms of the rate at which they kept their scheduled visits for HCC surveillance from July 2019 to May 2020. RESULTS: The percentage of kept scheduled visits was above 97% before February 2020. By contrast, it declined sharply after March 2020 when COVID‐19 became pandemic; the percentages were 75.5% in March, 63.0% in April and 49.1% in May 2020 (July 2019–February 2020 vs March–May 2020, P < 0.0001). Similar declines were observed in patients with cirrhosis or advanced fibrosis and in those with a history of HCC. Whereas most patients who cancelled a scheduled visit before February 2020 did not reschedule it, the majority of patients with cancellations after March 2020 did want to reschedule. CONCLUSIONS: The percentages of scheduled visits that were kept declined rapidly after COVID‐19 became pandemic in Japan, although the spread of COVID‐19 is relatively mild and the legal restriction of people's behaviour and movement is absent. Instituting measures to follow‐up with cancelled patients and resume surveillance will be necessary in the future.